5(6x+7)=28-(5x+7)

Simple and best practice solution for 5(6x+7)=28-(5x+7) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(6x+7)=28-(5x+7) equation:


Simplifying
5(6x + 7) = 28 + -1(5x + 7)

Reorder the terms:
5(7 + 6x) = 28 + -1(5x + 7)
(7 * 5 + 6x * 5) = 28 + -1(5x + 7)
(35 + 30x) = 28 + -1(5x + 7)

Reorder the terms:
35 + 30x = 28 + -1(7 + 5x)
35 + 30x = 28 + (7 * -1 + 5x * -1)
35 + 30x = 28 + (-7 + -5x)

Combine like terms: 28 + -7 = 21
35 + 30x = 21 + -5x

Solving
35 + 30x = 21 + -5x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '5x' to each side of the equation.
35 + 30x + 5x = 21 + -5x + 5x

Combine like terms: 30x + 5x = 35x
35 + 35x = 21 + -5x + 5x

Combine like terms: -5x + 5x = 0
35 + 35x = 21 + 0
35 + 35x = 21

Add '-35' to each side of the equation.
35 + -35 + 35x = 21 + -35

Combine like terms: 35 + -35 = 0
0 + 35x = 21 + -35
35x = 21 + -35

Combine like terms: 21 + -35 = -14
35x = -14

Divide each side by '35'.
x = -0.4

Simplifying
x = -0.4

See similar equations:

| 22+x=22-x | | -3(w-5)=-7w+31 | | -4+7(-7-5n)= | | -4u-3=9(u+4) | | -8(4+n)-8= | | 11x=222 | | 0.22y+0.03(y+4000)=2370 | | 3c+9c= | | q-9=-19 | | 4v-15=49 | | -9(v-4)=5v+4 | | .4x-73=90 | | -8(4+n)= | | 9-9=-19 | | 5+-(11)-(-11)= | | 15u+5v-3u+17v= | | -19+p=-9 | | 7(2x-10)-3=7(x-5)+4 | | -19+p=9 | | 8=16.9-a | | cosine(x)=-0.25 | | 8x-4(1+X)= | | 10=.11(0)+b | | X*x+1=101 | | 6/5÷6/ | | 2x+3+x=128 | | F(x)=log(x+7)+4 | | 6/5÷6/8 | | 7x-6+10x-5= | | 3c+12=5c+11.44 | | 6(-7d+12d)= | | -6w+8=-2(w+8) |

Equations solver categories